Risorse in rete per lo sviluppo della competenza testuale. Riviste e giornali russi online - Macagno, Claudio Gabriele (Educazione Linguistica Language Education, 2019)
This work represents the next step on the path that began with previous studies, where we focused on the advantages and disadvantages connected with the use of online resources to learn and teach Russian. In the present essay we consider how websites and online resources can help to develop textual competence. Some new online resources will be analysed and we will examine how they can be used to develop textual competence. The purpose is to increase the inventory of sites and make it available to learners and teachers. In particular, we will dwell upon Tekstoteka CMO MGU and the use of online Russian newspapers and journals for the development of textual competence.